Potential of wastewater reuse to alleviate water scarcity under future warming scenarios - Myla Kahn; Matteo Sangiorgio; Lorenzo Rosa (Environmental Research Letters, 2025)
Water scarcity is a critical issue, expected to worsen with global warming. Tackling water scarcity requires strategies to both decrease water consumption and enhance water availability. One promising solution to mitigate water scarcity is wastewater reuse, which involves collecting, treating, and repurposing used water. By employing a water balance model in conjunction with climate model outputs, we quantified the potential of wastewater reuse to reduce water gaps—situations where water consumption exceeds renewable water availability—under a baseline climate and two warming scenarios. We find that wastewater reuse could reduce the global water gap by 9.1% (from 457.9 to 416.1 km ^3 per year) under a baseline climate and by 8.3% in a 3 °C warming scenario (from 524.6 to 480.9 km ^3 per year). Our analysis highlights the potential for wastewater reuse to alleviate water gaps in water scarce countries and metropolitan areas. India, facing the world’s largest water gap, could reduce its baseline water gap by 6.6% (8.2 km ^3 per year) reusing all available wastewater, compared to a 1.2% (1.5 km ^3 per year) reduction with reuse of only currently treated wastewater. Specifically, in Delhi, India, the water gap could be reduced by 29.6% with full wastewater reuse and by 16.6% with the reuse of currently treated wastewater. As the global water gap widens with climate change, wastewater reuse is a promising solution to assure sustainable water access. Drawing attention to global disparities in access to wastewater treatment, our findings can guide targeted investments in wastewater treatment and reuse, aiming to alleviate water scarcity, reduce pollution from untreated wastewater, and support circular economies, ultimately ensuring sustainable access to water and sanitation.